Balloon pulmonary angioplasty for inoperable patients with chronic thromboembolic disease. (1st January 2018) - Wiedenroth, Christoph B.; Olsson, Karen M.; Guth, Stefan; Breithecker, Andreas; Haas, Moritz; Kamp, Jan‐Christopher; Fuge, Jan; Hinrichs, Jan B.; Roller, Fritz; Hamm, Christian W.; Mayer, Eckhard; Ghofrani, Hossein A.; et al.
Abstract : Symptomatic patients with residual pulmonary perfusion defects or vascular lesions but no pulmonary hypertension at rest are diagnosed with chronic thromboembolic disease (CTED). Balloon pulmonary angioplasty (BPA) is an emerging treatment for patients with inoperable chronic thromboembolic pulmonary hypertension (CTEPH), but data regarding the safety and efficacy of BPA in patients with CTED are lacking. We report a prospective series of ten consecutive patients with CTED who underwent 35 BPA interventions (median of four per patient) at two German institutions. All patients underwent a comprehensive diagnostic workup at baseline and 24 weeks after their last intervention. BPA was safe, with one pulmonary vascular injury and subsequent self‐limiting pulmonary bleeding as the only complication (2.9% of the interventions, 10% of the patients). After the procedures, World Health Organization functional class, 6‐min walking distance, pulmonary vascular resistance, and pulmonary arterial compliance improved, and NT‐proBNP concentrations declined in 9/10 patients. BPA may be a new treatment option for carefully selected patients with CTED. A larger, prospective, international registry is required to confirm these results.